The dangerous gift - Sutherland, Tui, 1978- (Sutherland, Tui, 1978- Wings of fire, 2022)
As the new queen of the dragon IceWings, Snowfall thinks the task of keeping her subjects within the boarders will be easy. However, when another dragon tribe shows up on her border seeking asylum, Snowfall must decide if they are trustworthy and if she'll be risking her dragons' safety by letting them in.